2019
DOI: 10.1200/jgo.19.00106
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life During Chemotherapy for Breast Cancer in a West African Population in Dakar, Senegal: A Prospective Study

Abstract: PURPOSE The prevalence of breast cancer is increasing in low- to middle-income countries such as Senegal. Our prospective study assessed the quality of life (QoL) of patients with breast cancer undergoing chemotherapy in Senegal. PATIENTS AND METHODS Our study included women with breast cancer undergoing chemotherapy as initial treatment at the Center Aristide Le Dantec University Hospital in Dakar. Clinical, sociodemographic, and QoL data were collected and analyzed at three different times: baseline, 3 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
1
9
0
1
Order By: Relevance
“…While not the primary interest of this study, it is notable that >60% of participants reported at least one grade 3 or higher chemotherapy-related symptom, and >75% of participants reported DT scores ≥4. Chemotherapy adverse event (AE) rates in sub-Saharan African populations are rarely published, but our findings are consistent with the >70% rate of grade 3-5 events at one hospital in Ethiopia and much higher than the ~30% grade 3-4 event rate among breast cancer patients treated in Senegal [35,36]. Self-reported grade 3-4 AEs rates are comparable in high-income countries as well, with two studies from United States and one from Australia reporting rates at 63%, 51% and 62%, respectively [7,37,38].…”
Section: Discussionsupporting
confidence: 86%
“…While not the primary interest of this study, it is notable that >60% of participants reported at least one grade 3 or higher chemotherapy-related symptom, and >75% of participants reported DT scores ≥4. Chemotherapy adverse event (AE) rates in sub-Saharan African populations are rarely published, but our findings are consistent with the >70% rate of grade 3-5 events at one hospital in Ethiopia and much higher than the ~30% grade 3-4 event rate among breast cancer patients treated in Senegal [35,36]. Self-reported grade 3-4 AEs rates are comparable in high-income countries as well, with two studies from United States and one from Australia reporting rates at 63%, 51% and 62%, respectively [7,37,38].…”
Section: Discussionsupporting
confidence: 86%
“…When these toxicities occur over a prolonged time and in a greater degree of severity, they may cause the interruption of the treatment [ 9 ]. Moreover, there is a worsening of the quality of life [ 10 , 11 , 12 ] which seems to be associated with a less favorable clinical prognosis and increased risk of recurrence [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the included studies were retrospective studies ( n = 77, 55.8%) of mostly registries and patient files ( 6 , 10 , 24 98 ) followed by cross-sectional studies ( n = 51, 36.9%) ( 99 149 ), systematic reviews ( n = 5, 3.6%) ( 2 , 150 153 ) and reviews ( n = 2, 2.1%) ( 154 , 155 ). There were two prospective studies ( 156 , 157 ) and one modeling study ( 158 ) ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…We also found studies conducted in Ghana ( n = 6) ( 50 , 71 , 111 , 123 , 134 , 155 ), Kenya ( n = 5) ( 70 , 96 , 115 , 132 , 139 ), Zambia ( n = 4) ( 44 , 77 , 102 , 126 ), and Eritrea ( n = 3) ( 60 62 ). There were seven countries with two studies each [Botswana ( 43 , 47 ), the Central African Republic ( 31 , 32 ), Mozambique ( 57 , 58 ), Rwanda ( 130 , 136 ), Senegal ( 147 , 156 ), Sudan ( 84 , 114 ) and Zimbabwe ( 38 , 39 )]. The countries with a single study were Cote d'Ivoire ( 128 ), Democratic Republic of Congo ( 99 ), Mali ( 85 ), Swaziland ( 76 ), Tanzania ( 49 ), and The Gambia ( 30 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation